Species richness influences the spatial distribution of trees in European forests. Issue 3 (20th December 2019) - Bastias, Cristina C.; Truchado, Daniel A.; Valladares, Fernando; Benavides, Raquel; Bouriaud, Olivier; Bruelheide, Helge; Coppi, Andrea; Finér, Leena; Gimeno, Teresa E.; Jaroszewicz, Bogdan; Scherer‐Lorenzen, Michael; Selvi, Federico; et al.
Abstract : The functioning of plant communities is strongly influenced by the number of species in the community and their spatial arrangement. This is because plants interact with their nearest neighbors and this interaction is expected to be stronger when the interacting individuals are ecologically similar in terms of resource use. Recent evidence shows that species richness alters the balance of intra‐ versus interspecific competition, but the effect of species richness, and phylogenetic and functional diversity on the spatial pattern of the plant communities remain less studied. Even far, how forest stand structure derived from past management practices can influence the relationship between species richness and spatial pattern is still unknown. Here, we evaluate the spatial distribution of woody individuals (DBH >7.5 cm) in 209 forest stands (i.e. plots) with an increasing level of species richness (from 1 up to 10 species) in six forest types along a latitudinal gradient in Europe. We used completely mapped plots to investigate the spatial pattern in each forest stand with point pattern techniques. We fitted linear models to analyze the effect of species richness (positively correlated with phylogenetic diversity) and functional diversity on tree spatial arrangements. We also controled this relationship by forest type and stand structure as a proxy of the management legacy. Our results showed a generalized positive effect of species richness and functional diversity on the degree of spatial clustering of trees, and on the spatial independence of tree sizes regardless of the forest type. Moreover, current tree spatial arrangements were still conditioned by its history of management; however its effect was independent of the number of species in the community. Our study showed that species richness and functional diversity are relevant attributes of forests influencing the spatial pattern of plant communities, and consequently forest functioning.